Relation of NCD Clinic’s Quality Improvement in Hypertension and Diabetes Care - คงประเสริฐ จุรีพร (Journal of Health Science of Thailand, 2022)
This cross-sectional study aimed to determine the association between the NCD clinic’s quality improvement and the hypertensive and diabetic patient’s clinical outcome. Relevant secondary data were collected from 896 hospitals under Office of the Permanent Secretary, Ministry of Public Health, that reported NCD clinic plus assessment results on the NCD Clinic Plus Online data system during June to August 2021. Two sets of variables were collected comprising of (A) the six elements of quality improvement: health care organization, clinical information systems, delivery system design, self-management support, decision support and community linkage; and (B) the two clinical outcome indicators: percentage of controllable blood pressure in hypertensive patients and blood glucose in diabetic patients. The data were analyzed by using frequency, mean, standard deviation, Pearson correlation coefficient and multiple linear regression (Enter Method). The findings revealed that there was significant positive correlation within the six elements of quality improvement (p<0.05) in all hospitals regardless of size. The correlation of overall elements to the percentages of controllable blood pressure among hypertensive patients in large, medium and small hospitals was at 33, 31.1, 26.7%, respectively; and that to the percentages of controllable blood glucose patient was at 23.0, 18.9, 14.1%, respectively. The elements of quality improvement that significantly related to the desirable blood pressure outcome were the community linkage element in large hospitals, the decision support, and community linkage element in small hospitals (p<0.05). The only element of quality improvement that significantly associated with the positive blood glucose outcome was on the community linkage in small size hospitals (p<0.05). The results of this study should be considered for planning in continuous quality improvement of NCD clinics with the context and the hospital size